Declamationes Sullanae. - Vives, Juan Luis, 1492-1540 (Vives, Juan Luis, 1492-1540. Works., 2012)
This is a critical, annotated, bilingual edition of Declamations 3,4, and 5, comprising the abdication speech of the Roman Republican dictator Sulla, followed by Lepidus the new consul's two unrestrained attacks on Sulla's morals, henchmen, and political program.